Associations of plasma phosphorylated tau181 and neurofilament light chain with brain amyloid burden and cognition in objectively defined subtle cognitive decline patients. (8th September 2022) - Huang, Yanlu; Li, Yuehua; Xie, Fang; Guo, Qihao
Abstract: Aims: There is increasing evidence that plasma biomarkers are specific biomarkers for Alzheimer's disease (AD) pathology, but their potential utility in Obj‐SCD (objectively defined subtle cognitive decline) remains unclear. Methods: A total of 234 subjects, including 65 with brain amyloid beta (Aβ) negative normal cognition (Aβ− NC), 58 with Aβ‐positive NC (Aβ+ NC), 63 with Aβ− Obj‐SCD, and 48 with Aβ+ Obj‐SCD were enrolled. Plasma Aβ42, Aβ40, Aβ42/Aβ40 ratio, phosphorylated tau181 (p‐tau181), neurofilament light chain (NfL), and total tau (T‐tau) were measured using Simoa assays. Logistic and linear regression analyses were used to examine the relationship between plasma biomarkers and brain amyloid, cognition, and imaging measures adjusting for age, sex, education, APOE ε4 status, and vascular risk scores. Receiver operating characteristics were used to evaluate the discriminative validity of biomarkers. Results: After adjustment, only plasma p‐tau181 and NfL were significantly elevated in Aβ+ Obj‐SCD participants compared to Aβ− NC group. Elevated p‐tau181 was associated with brain amyloid accumulation, worse cognitive performance (visual episodic memory, executive function, and visuospatial function), and hippocampal atrophy. These associations mainly occurred in Aβ+ individuals. In contrast, higher NfL was correlated with brain amyloid burden and verbal memory decline. These associations predominantly occurred in Aβ− individuals. The adjusted diagnostic model combining p‐tau181 and NfL levels showed the best performance in identifying Aβ+ Obj‐SCD from Aβ− NC [area under the curve (AUC) = 0.814], which did not differ from the adjusted p‐tau181 model (AUC = 0.763). Conclusions: Our findings highlight that plasma p‐tau181, alone or combined with NfL, contributes to identifying high‐risk AD populations. Abstract : This study provides strong support for using plasma biomarkers to identify potential risks for early Alzheimer's disease (AD). The figure presents the combination of plasma p‐tau181 and NfL can effectively identify AD pathology Obj‐SCD (objectively defined subtle cognitive decline).